The efficacy of picture vs. word danger cues in reducing imitation of dangerous actions in children - Dong, Shuanglong; Zhao, Liang; Bian, Zhaobin; Wang, Yansong (Frontiers in Psychology, 2024)
Introduction Children are naturally curious and often have limited self-control, leading them to imitate both safe and dangerous actions. This study aimed to investigate whether dangerous cues could effectively inhibit children’s imitation of hazardous behaviors and to compare the effectiveness of picture cues versus word cues in reducing this imitation. Methods Seventy-six children were divided into two groups: one group received picture cues, and the other received word cues. Both groups observed an agent grasping an object and were instructed to perform a corresponding keystroke response when a number appeared. A comparable group of adults was also included for reference. Results The results demonstrated that picture cues were significantly more effective than word cues in reducing the children’s tendency to imitate dangerous actions. Discussion These findings suggest that picture cues are a more effective method for preventing imitation of risky behaviors in children, which has important implications for improving safety education and accident prevention strategies through the use of visual danger cues.